globalization and the sources of global chaos (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Today, at least thirty years ago, the world has become a global village against the backdrop of the fall of other political-economic regimes in the south and east of the world, not to mention the reason for the unparalleled technological progress that capitalism has led to, successively, in recent times. Which established what will later be referred to as "capitalist globalization". As long as globalization is a capitalist phenomenon, polarization is its necessary essence, and polarization here is not just class polarization at the national level, but also national polarization at the global level, in the first place. Polarization, as the essence of capitalist globalization, has multiple manifestations that multiply its contradictions at the global and regional levels and within each of the many regions and countries of the world. The manifestations of polarization emerge as inevitable sources of chaos on all of these levels, which objectively raises the question of whether capitalist globalization, especially in its current stage of development, is a global system or global chaos.